Restriction enzyme analysis of cytomegalovirus DNA to study transmission of infection. Issue 3 (March 1986) - Peckham, C S; Garrett, A J; Chin, K S; Preece, P M; Nelson, D B; Warren, D E
Abstract : Restriction enzyme analysis of cytomegalovirus deoxyribonucleic acid (DNA) has been used to characterise virus isolates and has provided information on patterns of viral transmission. It was shown that virus isolated from a congenitally infected infant was unlikely to have originated from the 13 congenitally infected children with whom the mother, a nurse, had been in contact. Of nine mother and infant pairs, from whom cytomegalovirus was isolated, seven yielded strains that were indistinguishable for mother and child; one pair showed minor differences and one was clearly distinguishable. Virus isolates from seven children attending a day nursery were typed, and only siblings were excreting similar strains of cytomegalovirus. Further examples of the application of this technique to studies of cytomegalovirus in a family environment are given. It is concluded that characterisation of virus strains by restriction analysis of DNA is a valuable epidemiological tool.